A Study of Morphological and Thermal Properties of Polylactic Acid (PLA) Modified MMT (Ion Exchange Method) Nanocomposite - Wan Siti Noorhashimah, Wan Kamaruzaman (2013)
Polylactic (PLA) is a thermoplastic aliphatic polyester produced by the ring opening polymerization of lactide. PLA is more suitable because it is made from renewable sources and its properties are friendly to the environment. A series of biodegradable PLA nanocomposites using modified organoclay. The type of modication is by ion exchange method and were prepared by melt compounding using a Brabender twin screw extruder. Then, the morphology of exfoliated PLA modified nanocomposite was observed using X-ray Diffraction (XRD) analysis and Scanning Electron Miscoscpy (SEM) analysis. By modification of PLA will affect the structure of nanocomposite from agglomerates to become intercalated nanocomposite or exfoliated nanocomposite. Besides that, the melting temperature of PLA modified nanocomposite should be increase after modification from original temperature 160℃ to become 170℃.